Values of Pancasila Student Profile in the Novel "Humairah and Alfarisi" by Nurul Khaira Sabila - Aida Fitriani; Main Sufanti (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to identify the values of the Pancasila student profile contained in the novel "Humairah & Alfarisi" by Nurul Khairul Sabila. This research uses descriptive qualitative method. The data source of this research is the novel "Humaira & Alfarisi" by Nurul Khairul Sabila, the second printing of which amounted to 432 pages and was published in 2018 by Wahyu Qolbi Publisher. The data in this study are the story text and dialog contained in the novel "Humaira and Alfarisi" by Nurul Khaira Sabila. The data collection techniques used in the research are reading, recording, and data reduction techniques. The validation technique in this research uses data triangulation including triangulation of methods and theories. Data analysis techniques in this research are data comparison, categorization, and inference. Based on the results of the study, it shows that the novel "Humaira and Alfarisi" by Nurul Khaira Sabila contains several values of the Pancasila student profile, including. (1) The dimension of faith, fear of God, and noble character contains elements of religious morals, personal morals, and morals to humans. (2) The dimension of working together which contains elements of collaboration, caring, sharing, giving, and receiving. (3) An independent dimension containing elements of self-awareness. (4) A critical reasoning dimension containing elements of curiosity.